Study guides

☆☆

Q: Simplify x - 2x plus 3?

Write your answer...

Submit

Still have questions?

Related questions

-7 + 2(x-3) = -7+2x-6 = 2x - 13

3(x+y)

Simplify 4x + 3 = 2x + 8 2x = 5 x =2½

x(x + 2)

Without parentheses, 3 x 4 = 12 2x + 12 factors to 2(x + 6)

2

-3

If there are no equals you can simplify this by collecting all the x values together and use the addition property of signed numbers. 2x+4x-5x+x=2x; 4+3=7. 2x+7 is the simplified statement.

3 * x + 4 + 2xMDAS rule:3x + 4 + 2x5x + 4

X = 0.8

2x = x+3 2x-x = 3 x = 3

Factor it out: (x+2) squared

you need to reorder the problem by manipulating the numbers -2x-7=-x+13 group your variables and constants thus -x-2x=7+13 simplify -3x=20 simplify again x=-20/3

5x+2x-3y+y = (5+2)x+(-3+1)y = 7x - 2y

8x4

3x^2 + x + 2x^2 = 5x^2 + x

(2x + 3)(x + 1 ) = 2x^2 +5x +3

I assume you wish to simplify the expression (x - 2)/(3x + 9) . (2x + 6)/(2x - 4) = (x - 2)(2x + 6) / [(3x + 9)(2x - 4)] = 2(x - 2)(x + 3) / [6(x + 3)(x - 2)] = 1/3.

2x + 8 + x = 2x + 15 simplify 2x to both sides since they have the same sign8 + x = 15 subtract 8 to both sidesx = 7

2x + 3 = x 2x + 3 - 3 = x - 3 2x = x - 3 2x - x = x - 3 - x x = -3

x+3(x+1)=2x x + 3x + 3 = 2x 2x + 3 = 0 2x = -3 or x = -1.5

3 + 3 + 2x = 0 6 + 2x = 0 2x = -6 x = -6/2 x = -3

x+5+x+3 can be simplified to: 2x+8

x - 3x + 4 = 3 - 9 simplify -2x + 4 = -6 -4 -4 -2x = -10 /-2 /-2 x = 5

2x=x+3=x=3